How Trajectories of Reasons for Alcohol Use Relate to Trajectories of Binge Drinking: National Panel Data Spanning Late Adolescence to Early Adulthood - Patrick, Megan E. (2011)
Developmental changes in both alcohol use behaviors and self-reported reasons for alcohol use were investigated. Participants were surveyed every two years from ages 18 to 30 as part of the Monitoring the Future national study (analytic weighted sample size N=9,308; 53% women, 40% college attenders). Latent growth models were used to examine correlations among trajectories of binge drinking and trajectories of self-reported reasons for alcohol use across young adulthood. Results revealed developmental changes in reasons for use and correlations between the patterns of within-person change in frequency of binge drinking and within-person change in reasons for use. In particular, an increase in binge drinking between ages 18 and 22 was most positively correlated with slopes of using alcohol to get high and because of boredom. Continued binge drinking between ages 22 and 30 was most strongly correlated with using alcohol to get away from problems. Almost no moderation by gender, race, college attendance, employment, or marital status was found. Binge drinking and reasons for alcohol use traveled together, illustrating the ongoing and dynamic connections between changes in binge drinking and changes in reasons for use across late adolescence and early adulthood.